A postcolonial reading of the early life of Sara Baartman and the Samaritan Woman in John 4 - Dewald E. Jacobs (HTS Teologiese Studies/Theological Studies, 2024)
When Jesus meets the Samaritan Woman at Jacob’s well in John 4, it is a meeting between two colonial subjects in the Roman Empire. In this encounter we find the Samaritan Woman as a triply marginalised body, a woman subject to multiple, intersecting forms of oppression within her patriarchal context. Identified as a Samaritan Woman, Jewish rabbis regarded her as unclean, impure, and being menstruous from birth. It can also be deduced that she is an outcast in her own society because she comes to draw from the well at noon, the hottest part of the day when people did not usually fetch water. This Samaritan Woman is nameless, landless and powerless in an imperial, colonial and patriarchal context. The poem of Diana Ferrus, I’ve come to take you home, in memory of Sarah Baartman, highlights how Baartman was dehumanised and treated as a sexual object by European colonisers. Through a postcolonial reading of John 4, I consider the intersections between the Samaritan Woman and the early life of Sara Baartman in their respective colonial contexts and invite the reader, as the poem invites Baartman, to come home to Africa and resist Western European imperial and colonial patterns and tendencies.